Research on appliance event detection method based on intelligent perception technology - Ziyuan YANG; Xiaobin XU; Xin LI; Yimeng ZHAO (物联网学报)
The rapid development of Internet of things and intelligent technologies provides the system support for intelligent load perception technology of power usage,as well as provides analytical data for power user behavior.In order to realize the accurate identification of equipment start or stop events,a technical proposal which combined the high frequency and high precision power data with the dynamic time consolidation (DTW) algorithm was proposed,and an experimental testing platform based on the independent hardware was built.The experimental results show that the power incident identification algorithm has a high identification accuracy and recall rate,which can be applied in more scenarios to realize the full perception of power load.